TOG‘AYLI BALIQLAR MAVZUSINI MULTIMEDIA VA VIRTUAL LABORATORIYA ASOSIDA O‘QITISH METODIKASI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This chapter thoroughly analyzes the methodology of utilizing multimedia and virtual laboratory (VL) technologies for teaching the topic of cartilaginous fish (Chondrichthyes). The limitations of traditional teaching methods, particularly difficulties in visualizing and comprehending complex biological structures, are identified as a primary challenge. The study aims to develop an innovative methodology and present its theoretical foundations to enhance the effectiveness of teaching cartilaginous fish biology. The chapter discusses the pedagogical advantages of multimedia and VL, their integration steps into the educational process, and the structure and implementation approaches of the developed module. Findings and discussion demonstrate the positive impact of this methodology on students' knowledge acquisition, interest, and motivation.